Potential immediate hypersensitivity reactions following immunization in preschool aged children in Victoria, Australia - C.-M. Baxter; H. J. Clothier; K. P. Perrett (Taylor & Francis Group, 2018)
Immediate hypersensitivity reactions (IHR) are rare but potentially serious adverse events following immunization (AEFI). Surveillance of Adverse Events following Vaccination in the Community (SAEFVIC) is an enhanced passive surveillance system that collects, analyses and reports information about AEFI in Victoria, Australia. We describe the incidence, timing and type of potential IHR following vaccination in preschool children reported over an 8-year period. A total of 2110 AEFI were reported in 1620 children, of which 23.5% (496) were classified as potential IHR. Of these, 37.1% (184) were suspected to be IgE-mediated, (including anaphylaxis, angioedema and/or urticaria) and 83.5% (414) occurred within 15 minutes of vaccination. The incidence of potential IHR was 5.4 per 100,000 doses, with that of suspected IgE-mediated IHR being 2.0 per 100,000 doses. The incidence of anaphylaxis was extremely low (0.13 per 100,000 doses) and is consistent with other published studies. Potential IHR following immunization should be reported to appropriate local pharmacovigilance systems and patients reviewed by specialists able to evaluate, investigate and manage future vaccinations.